TAIGA—A hybrid array for high-energy gamma astronomy and cosmic-ray physics - Budnev, N.; Astapov, I. I.; Garmash, A.; Grebenyuk, V.; Gress, O.; Gress, T.; Grinyuk, A.; Grishin, O.; Horns, D.; Ivanova, A.; Kalmykov, N.; Kazarina, Yu.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
The combination of a wide angle timing Cherenkov array and Imaging Atmospheric Cherenkov Telescopes operated in mono mode offers a cost-effective way to construct a few square kilometers array for ultrahigh-energy gamma astronomy. The first stage of the TAIGA Observatory (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) is described here. It will comprise TAIGA-HiSCORE - 120 wide angle Cherenkov stations distributed over an area of 1.0 km 2 and three IACTs (TAIGA-IACT).